AB co-doped perovskite nanofiber catalyst and preparation method and application thereof
Patent Information
- Application Number
- CN202310339335.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-03
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2043-04-03
AI Technical Summary
其目的一方面是解决现有贵金属催化剂中贵金属稀缺、价格昂贵、抗中毒性差的技术问题;另一方面是解决现有钙钛矿材料催化剂所存在的稳定性和催化性较差的技术问题
[0020] This invention utilizes strontium doping at the A-site and iridium doping at the B-site to prepare iron-based perovskite with AB-site co-doping, thereby improving the oxygen evolution capacity of the catalyst in OER. Furthermore, the catalyst is prepared by electrospinning and calcination, which not only reduces cost and the amount of precious metals used, but also eliminates environmental pollution and allows for large-scale preparation.
Smart Images

Figure CN116288461B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrochemical energy storage and new energy technology, and in particular to an AB-site co-doped perovskite nanofiber catalyst, its preparation method, and its application. Background Technology
[0002] The overexploitation of traditional fossil fuels such as coal, oil, and natural gas has caused severe environmental pollution. For many years, to alleviate environmental pollution and the energy crisis caused by the increasing depletion of non-renewable energy sources, people have developed many technologies to reduce energy consumption, aiming for more rational and efficient energy use and reduced pollutant emissions. Therefore, developing and utilizing efficient and low-cost clean energy is the main way to replace fossil fuels and alleviate environmental pollution problems. People are paying increasing attention to the application of renewable energy sources such as hydropower, tidal energy, solar energy, and hydrogen energy. However, intermittent energy sources such as solar, tidal, and wind energy are affected by various factors and cannot be continuously generated, hindering the sustainable use of energy in daily life and production. Therefore, if surplus energy can be stored when intermittent energy is abundant and used when needed, the above problems can be effectively solved. Hydrogen, as a clean energy carrier, has the characteristics of abundant reserves, high calorific value, and zero carbon emissions, and can also be used to produce high-value chemicals. Electrochemical water splitting to produce hydrogen can achieve both the full utilization of sustainable renewable energy and zero carbon emissions.
[0003] The oxygen evolution reaction (OER) is a crucial half-reaction in the electrochemical process of water splitting to produce hydrogen fuel, converting electrical energy into hydrogen. The electrical energy used can come from intermittent energy sources such as solar, tidal, and wind power. However, due to the slow kinetics and high catalytic barrier of OER, a large overpotential is typically required to drive water splitting. Therefore, optimizing the performance of OER electrocatalysts is essential for improving the efficiency of electrochemical water splitting for hydrogen production. Suitable catalysts can make the process more efficient and energy-saving. To reduce the overpotential and improve efficiency, the development of efficient OER electrocatalysts has become a current research hotspot. Iridium dioxide (IrO2) and ruthenium dioxide (RuO2) are recognized as commercially available OER catalysts with excellent catalytic performance. However, iridium and ruthenium are both rare precious metals found in the Earth's crust, resulting in high operating costs due to their high price. Furthermore, their poor stability severely limits their large-scale application. Therefore, developing efficient, low-cost, abundant, and stable catalysts is crucial.
[0004] In recent years, the OER activity and stability of transition metals and their compounds in alkaline solutions have been extensively studied. Perovskite (ABO3, where the A-site at the 12-coordinate is usually a rare earth or alkali metal, and the B-site at the 6-coordinate is usually a transition metal) is considered one of the most promising OER catalysts due to its low cost, tunable composition, stable structure, and high activity. However, in industrial applications, the inherent OER catalytic performance of perovskite is unsatisfactory, especially its electrocatalytic ability and stability under alkaline conditions.
[0005] Therefore, how to provide a perovskite nanofiber catalyst with good stability and high catalytic activity has become an urgent problem to be solved by those skilled in the art. Summary of the Invention
[0006] In view of this, the present invention provides an AB-site co-doped perovskite nanofiber catalyst, its preparation method, and its application. Its purpose is twofold: firstly, to address the technical problems of scarcity, high cost, and poor resistance to poisoning in existing noble metal catalysts; and secondly, to solve the technical problems of poor stability and catalytic activity in existing perovskite material catalysts.
[0007] To achieve the above objectives, the present invention adopts the following technical solution:
[0008] This invention provides a method for preparing AB-site co-doped perovskite nanofiber catalysts, comprising the following steps:
[0009] S1. A polymer solution is obtained by mixing lanthanum nitrate hexahydrate, strontium nitrate, ferric nitrate nonahydrate, iridium trichloride, N,N-dimethylformamide and polyvinylpyrrolidone.
[0010] S2. Electrospinning is performed on the polymer solution to obtain nanofiber polymer precursors;
[0011] S3. The calcination treatment of the nanofiber polymer precursor yields the AB-site co-doped perovskite nanofiber catalyst.
[0012] Furthermore, the molar volume ratio of lanthanum nitrate hexahydrate, strontium nitrate, ferric nitrate nonahydrate, iridium trichloride, and N,N-dimethylformamide is 0.5–1.0 mmol: 0.5–1.0 mmol: 1.38–1.47 mmol: 0.03–0.12 mmol: 10–15 mL; and the mass-volume ratio of polyvinylpyrrolidone and N,N-dimethylformamide is 1–2 g: 10–15 mL.
[0013] Furthermore, in step S1, the mixing temperature is 40–60°C, and the mixing time is 8–15 hours.
[0014] Furthermore, the parameters for the electrospinning process are as follows: injection speed of 0.4–0.6 mL / h, distance between needle tip and collection device of 15–18 cm, and operating voltage of 15–18 kV.
[0015] Furthermore, the calcination treatment is divided into two stages: the temperature of the first stage is 200-300℃ and the holding time of the first stage is 1.5-2.5h; the temperature of the second stage is 750-850℃ and the holding time of the second stage is 2.5-3.5h.
[0016] Furthermore, the heating rate from room temperature to the temperature of the first stage is 1–5 °C / min, and the heating rate from the temperature of the first stage to the temperature of the second stage is 1–5 °C / min.
[0017] This invention provides an AB-site co-doped perovskite nanofiber catalyst prepared by the above preparation method.
[0018] This invention also provides the application of the above-mentioned AB-site co-doped perovskite nanofiber catalyst in the oxygen evolution reaction.
[0019] As can be seen from the above technical solution, compared with the prior art, the beneficial effects of the present invention are as follows:
[0020] This invention utilizes strontium doping at the A-site and iridium doping at the B-site to prepare iron-based perovskite with AB-site co-doping, thereby improving the oxygen evolution capacity of the catalyst in OER. Furthermore, the catalyst is prepared by electrospinning and calcination, which not only reduces cost and the amount of precious metals used, but also eliminates environmental pollution and allows for large-scale preparation.
[0021] This invention regulates the morphology of hollow nanofibers formed by the ratio of N,N-dimethylformamide and polyvinylpyrrolidone, thereby adjusting the oxygen evolution response (OER) of the catalyst. The hollow nanofiber perovskite catalyst with the best morphology, larger surface area, and more active sites is obtained when the mass-to-volume ratio of polyvinylpyrrolidone to N,N-dimethylformamide is 1–2 g: 10–15 mL. Attached Figure Description
[0022] Figure 1 This is the La prepared in Example 1 of the present invention. 0.6 Sr 0.4 Fe 0.96 Ir 0.04 O 3-σ A schematic diagram of the catalyst process;
[0023] Figure 2 This is the La prepared in Example 1 of the present invention. 0.6 Sr 0.4 Fe 0.96 Ir 0.04 O3-σ XRD pattern of the catalyst;
[0024] Figure 3 This is the La prepared in Example 1 of the present invention. 0.6 Sr 0.4 Fe 0.96 Ir 0.04 O 3-σ SEM image of the catalyst;
[0025] Figure 4 This is the La prepared in Example 1 of the present invention. 0.6 Sr 0.4 Fe 0.96 Ir 0.04 O 3-σ TEM image of the catalyst;
[0026] Figure 5 This is the La prepared in Example 1 of the present invention. 0.6 Sr 0.4 Fe 0.96 Ir 0.04 O 3-σ EDS energy spectrum of the catalyst;
[0027] Figure 6 This is a comparison chart showing the performance of the catalysts obtained in Examples 1-4 of this invention and the LaFeO3 catalyst in Comparative Example 1 in the catalytic oxygen evolution reaction.
[0028] Figure 7 This is the La prepared in Example 1 of the present invention. 0.6 Sr 0.4 Fe 0.96 Ir 0.04 O 3-σ Comparison of the performance of the catalyst and the commercial catalyst RuO2 in the oxygen evolution reaction. Detailed Implementation
[0029] This invention provides a method for preparing AB-site co-doped perovskite nanofiber catalysts, comprising the following steps:
[0030] S1. A polymer solution is obtained by mixing lanthanum nitrate hexahydrate, strontium nitrate, ferric nitrate nonahydrate, iridium trichloride, N,N-dimethylformamide and polyvinylpyrrolidone.
[0031] S2. Electrospinning is performed on the polymer solution to obtain nanofiber polymer precursors;
[0032] S3. The calcination treatment of the nanofiber polymer precursor yields the AB-site co-doped perovskite nanofiber catalyst.
[0033] In this invention, the molar volume ratio of lanthanum nitrate hexahydrate, strontium nitrate, ferric nitrate nonahydrate, iridium trichloride, and N,N-dimethylformamide is 0.5–1.0 mmol: 0.5–1.0 mmol: 1.38–1.47 mmol: 0.03–0.12 mmol: 10–15 mL, preferably 0.6–0.9 mmol: 0.6–0.9 mmol: 1.4–1.46 mmol: 0.05–0.1 mmol: 11–14 mL; more preferably 0.7–0.8 mmol: 0.7–0.8 mmol: 1.42–1.44 mmol: 0.06–0.08 mmol: 12–13 mL.
[0034] In this invention, the mass-to-volume ratio of polyvinylpyrrolidone and N,N-dimethylformamide is 1-2 g: 10-15 mL, preferably 1.2-1.8 g: 11-14 mL, and more preferably 1.4-1.6 g: 12-13 mL.
[0035] In this invention, the mixing temperature in step S1 is 40-60°C, preferably 45-55°C, and more preferably 48-52°C; the mixing time is 8-15 hours, preferably 9-14 hours, and more preferably 10-12 hours.
[0036] In this invention, the parameters of the electrospinning treatment are as follows: the injection rate is 0.4-0.6 mL / h, preferably 0.45-0.55 mL / h, and more preferably 0.55 mL / h; the distance between the needle tip and the collecting device is 15-18 cm, preferably 16-17 cm; and the working voltage is 15-18 kV, preferably 16-17 kV.
[0037] In this invention, the needle of the plastic syringe used for electrospinning is model 23-G.
[0038] In this invention, the receiving substrate of the collecting device is release paper.
[0039] In this invention, the calcination treatment is divided into two stages. The temperature of the first stage is 200-300℃, preferably 220-280℃, and more preferably 240-260℃. The holding time of the first stage is 1.5-2.5h, preferably 1.6-2.4h, and more preferably 1.8-2.2h. The temperature of the second stage is 750-850℃, preferably 770-830℃, and more preferably 780-800℃. The holding time of the second stage is 2.5-3.5h, preferably 2.7-3.2h, and more preferably 2.8-3.0h.
[0040] In this invention, the heating rate from room temperature to the temperature of the first stage is 1 to 5 °C / min, preferably 2 to 4 °C / min, and more preferably 3 °C / min; the heating rate from the temperature of the first stage to the temperature of the second stage is 1 to 5 °C / min, preferably 2 to 4 °C / min, and more preferably 3 °C / min.
[0041] This invention provides an AB-site co-doped perovskite nanofiber catalyst prepared by the above preparation method.
[0042] This invention also provides the application of the above-mentioned AB-site co-doped perovskite nanofiber catalyst in the oxygen evolution reaction.
[0043] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0044] Example 1
[0045] 0.9 mmol lanthanum nitrate hexahydrate, 0.6 mmol strontium nitrate, 1.44 mmol ferric nitrate nonahydrate, and 0.06 mmol iridium trichloride were added to a container containing 10 mL of N,N-dimethylformamide. The mixture was stirred in a water bath at 50 °C for 15 minutes until completely and uniformly dissolved. Then, 1.42 g of polyvinylpyrrolidone was added to the mixture, and the mixture was stirred for another 10 hours until uniformly dissolved, resulting in a viscous polymer solution.
[0046] The viscous polymer solution was transferred to a 10 mL plastic syringe for electrospinning. The electrospinning parameters were: injection rate of 0.5 mL / h, distance between needle tip and collection device of 15 cm, and working voltage of 15 kV. After the electrospinning process was completed, the release paper on the electrospinning receiving device was removed and the release paper was separated to obtain the nanofiber polymer precursor.
[0047] The nanofiber polymer precursor was calcined in a muffle furnace under air atmosphere, heated to 200°C at a rate of 2°C / min, and held for 2 hours. Then, the temperature was increased to 800°C at a rate of 2°C / min and held for 3 hours. After natural cooling to room temperature, the precursor was ground to obtain La. 0.6 Sr 0.4 Fe 0.96 Ir 0.04 O 3-σ catalyst.
[0048] Figure 2 This is the La prepared in this embodiment. 0.6 Sr 0.4 Fe0.96 Ir 0.04 O 3-σ The XRD pattern of the catalyst, by Figure 2 It can be seen that the diffraction peaks of the catalyst prepared by the present invention at different 2θ angles correspond to the standard PDF card, and there are no obvious impurity peaks, indicating that no secondary phase is generated.
[0049] Figure 3 This is the La prepared in this embodiment. 0.6 Sr 0.4 Fe 0.96 Ir 0.04 O 3-σ SEM images of the catalyst, by Figure 3 It can be seen that the catalyst prepared by the present invention has the morphology of hollow nanofibers;
[0050] Figure 4 This is the La prepared in this embodiment. 0.6 Sr 0.4 Fe 0.96 Ir 0.04 O 3-σ TEM image of the catalyst, by Figure 4 The morphology of the hollow nanofibers in the catalyst prepared by this invention can be seen more clearly.
[0051] Figure 5 This is the La prepared in Example 1 of the present invention. 0.6 Sr 0.4 Fe 0.96 Ir 0.04 O 3-σ The EDS spectrum of the catalyst, by Figure 5 It can be seen that the catalyst prepared by this invention does indeed contain La, Sr, Fe, Ir and O elements, which indicates that hollow nanofiber perovskite catalysts with A-site Sr doping and B-site Ir doping were successfully prepared by doping and electrospinning.
[0052] Example 2
[0053] 0.9 mmol lanthanum nitrate hexahydrate, 0.6 mmol strontium nitrate, 1.47 mmol ferric nitrate nonahydrate, and 0.03 mmol iridium trichloride were added to a container containing 10 mL of N,N-dimethylformamide. The mixture was stirred in a water bath at 40 °C for 20 minutes until completely and uniformly dissolved. Then, 1.42 g of polyvinylpyrrolidone was added to the mixture, and the mixture was stirred for another 10 hours until uniformly dissolved, resulting in a viscous polymer solution.
[0054] The viscous polymer solution was transferred to a 10 mL plastic syringe for electrospinning. The electrospinning parameters were: injection rate of 0.4 mL / h, distance between needle tip and collection device of 18 cm, and working voltage of 16 kV. After the electrospinning process was completed, the release paper on the electrospinning receiving device was removed and the release paper was separated to obtain the nanofiber polymer precursor.
[0055] The nanofiber polymer precursor was calcined in a muffle furnace under air atmosphere, heated to 300°C at a rate of 3°C / min, and held for 2 hours. Then, the temperature was increased to 750°C at a rate of 3°C / min and held for 3 hours. After natural cooling to room temperature, the precursor was ground to obtain La. 0.6 Sr 0.4 Fe 0.96 Ir 0.04 O 3-σ catalyst.
[0056] Example 3
[0057] 0.9 mmol lanthanum nitrate hexahydrate, 0.6 mmol strontium nitrate, 1.41 mmol ferric nitrate nonahydrate and 0.09 mmol iridium trichloride were added to a container containing 10 mL of N,N-dimethylformamide. The mixture was stirred in a water bath at 60 °C for 10 minutes until completely and uniformly dissolved. Then, 1.42 g of polyvinylpyrrolidone was added to the mixture, and the mixture was stirred for another 10 hours until uniformly dissolved to obtain a viscous polymer solution.
[0058] The viscous polymer solution was transferred to a 10 mL plastic syringe for electrospinning. The electrospinning parameters were: injection rate of 0.6 mL / h, distance between needle tip and collection device of 16 cm, and working voltage of 16 kV. After the electrospinning process was completed, the release paper on the electrospinning receiving device was removed and the release paper was separated to obtain the nanofiber polymer precursor.
[0059] The nanofiber polymer precursor was calcined in a muffle furnace under air, heated to 260°C at a rate of 2°C / min, and held for 2 hours. Then, the temperature was increased to 780°C at a rate of 2°C / min and held for 3 hours. After natural cooling to room temperature, the precursor was ground to obtain La. 0.6 Sr 0.4 Fe 0.96 Ir 0.04 O 3-σ catalyst.
[0060] Example 4
[0061] 0.9 mmol lanthanum nitrate hexahydrate, 0.6 mmol strontium nitrate, 1.38 mmol ferric nitrate nonahydrate, and 0.12 mmol iridium trichloride were added to a container containing 10 mL of N,N-dimethylformamide. The mixture was stirred in a water bath at 50 °C for 15 minutes until completely and uniformly dissolved. Then, 1.42 g of polyvinylpyrrolidone was added to the mixture, and the mixture was stirred for another 10 hours until uniformly dissolved, resulting in a viscous polymer solution.
[0062] The viscous polymer solution was transferred to a 10 mL plastic syringe for electrospinning. The electrospinning parameters were: injection rate of 0.5 mL / h, distance between needle tip and collection device of 15 cm, and working voltage of 18 kV. After the electrospinning process was completed, the release paper on the electrospinning receiving device was removed and the release paper was separated to obtain the nanofiber polymer precursor.
[0063] The nanofiber polymer precursor was calcined in a muffle furnace under air atmosphere, heated to 280°C at a rate of 4°C / min, and held for 2 hours. Then, the temperature was increased to 850°C at a rate of 5°C / min and held for 3 hours. After natural cooling to room temperature, the precursor was ground to obtain La. 0.6 Sr 0.4 Fe 0.96 Ir 0.04 O 3-σ catalyst.
[0064] Comparative Example 1
[0065] Iron-based perovskite catalysts were prepared using a traditional method: 10 mmol of lanthanum nitrate hexahydrate and 10 mmol of ferric nitrate nonahydrate were weighed and dissolved in 100 mL of deionized water. After mixing thoroughly, 40 mmol of citric acid and 20 mmol of ethylenediaminetetraacetic acid were added, and the mixture was stirred at room temperature until a homogeneous solution was formed. Then, ammonia was added dropwise to the solution until the pH value was equal to 8. The solution was heated and stirred in an 80°C water bath until a gel-like substance appeared. The resulting gel was placed in a muffle furnace and sintered at 250°C for 5 h to obtain a powder precursor. The powder precursor was then ground and sintered again in a muffle furnace at 900°C for 5 h to obtain the LaFeO3 perovskite catalyst.
[0066] Figure 6 This is a comparison chart showing the performance of the catalysts obtained in Examples 1-4 of this invention and the LaFeO3 catalyst in Comparative Example 1 in the catalytic oxygen evolution reaction. Figure 6 It can be seen that the La prepared by the present invention 0.6 Sr 0.4 Fe 0.96 Ir 0.04 O 3-σThe oxygen evolution capacity of the catalyst is significantly better than that of the LaFeO3 perovskite catalyst prepared by traditional methods, specifically as follows: at a current density of 10 mA·cm⁻¹ -2 La 0.6 Sr 0.4 Fe 0.96 Ir 0.04 O 3-σ The potential of the catalyst is significantly lower than that of the LaFeO3 perovskite catalyst, and the current density is significantly higher than that of the LaFeO3 perovskite catalyst. This indicates that A-site Sr doping, B-site Ir doping, and the morphology of hollow nanofibers can significantly improve the catalytic performance of rare earth iron-based perovskite oxides, thereby enhancing their ability to catalyze the oxygen evolution reaction.
[0067] Figure 7 This is the La prepared in Example 1 of the present invention. 0.6 Sr 0.4 Fe 0.96 Ir 0.04 O 3-σ A comparison chart of the performance of the catalyst and the commercial catalyst RuO2 in the catalytic oxygen evolution reaction, by [source missing]. Figure 7 As can be seen, the catalyst prepared by the present invention has excellent oxygen evolution catalytic performance, and its performance is close to that of the commercial noble metal catalyst RuO2. This shows that, under the condition of consistent catalytic performance, the technical solution described in the present invention requires a lower cost, and the catalyst of the present invention has a higher cost performance than the RuO2 catalyst.
[0068] The various embodiments in this specification are described in a progressive manner, with each embodiment focusing on the differences from other embodiments. The same or similar parts between the various embodiments can be referred to each other.
[0069] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing an AB-site co-doped perovskite hollow nanofiber catalyst for the oxygen evolution reaction, characterized in that, Includes the following steps: S1. A polymer solution is obtained by mixing lanthanum nitrate hexahydrate, strontium nitrate, ferric nitrate nonahydrate, iridium trichloride, N,N-dimethylformamide and polyvinylpyrrolidone. S2. Electrospinning is performed on the polymer solution to obtain nanofiber polymer precursors; S3. Calcining the nanofiber polymer precursor yields the AB-site co-doped perovskite hollow nanofiber catalyst. The molar volume ratio of lanthanum nitrate hexahydrate, strontium nitrate, ferric nitrate nonahydrate, iridium trichloride, and N,N-dimethylformamide is 0.5~1.0 mmol: 0.5~1.0 mmol: 1.38~1.47 mmol: 0.03~0.12 mmol: 10~15 mL; the mass-volume ratio of polyvinylpyrrolidone and N,N-dimethylformamide is 1~2 g: 10~15 mL.
2. The preparation method according to claim 1, characterized in that, The mixing temperature in step S1 is 40~60℃, and the mixing time is 8~15h.
3. The preparation method according to claim 1 or 2, characterized in that, The parameters for the electrospinning process are as follows: injection rate of 0.4~0.6 mL / h, distance between needle tip and collection device of 15~18 cm, and working voltage of 15~18 kV.
4. The preparation method according to claim 3, characterized in that, The calcination process is divided into two stages. The temperature of the first stage is 200~300℃ and the holding time of the first stage is 1.5~2.5h. The temperature of the second stage is 750~850℃ and the holding time of the second stage is 2.5~3.5h.
5. The preparation method according to claim 4, characterized in that, The heating rate from room temperature to the temperature of the first stage is 1~5℃ / min, and the heating rate from the temperature of the first stage to the temperature of the second stage is 1~5℃ / min.
6. The AB-site co-doped perovskite hollow nanofiber catalyst prepared by the preparation method according to any one of claims 1 to 5.
7. The application of the AB-site co-doped perovskite hollow nanofiber catalyst according to claim 6 in the oxygen evolution reaction.
Citation Information
Patent Citations
Preparation method of precious metal doped composite ABO3-type catalyst
CN102133546A
Ir-doped SrRuO3 doped material, preparation method and application
CN109911950A